The friendship of five New England poets - Spilman, Clara (My University, 1900)
Introduction: Of all the sacred relations existing among men, none is more sacred and inspiring than that of friendship. It should be cultivated and cherished for more than any other relation, it develops and enriches a man’s life—creates in him lofty ideals and noble aspirations and fosters a desire to constantly make these yet nobler and more lofty. The truest friendship can exist only in pure and loving hearts—in those whose lives are upright and good—whose natures are responsive to the highest and tenderest feelings in man, and whose characters are such as to bring out and produce these feelings in others. Sincerity, thruthfulness and the sympathetic spirit are characteristics and one who possess these, will exert an unbounded influence for good; for their natures will react on all those with whom they come in contact.
Citation: Spilman, Clara. The friendship of five New England poets. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Friendship; New England; Emerson; Longfellow; Whittier; Holmes; Lowell; Theses; Manuscripts (documents)